2022
DOI: 10.26717/bjstr.2022.42.006770
|View full text |Cite
|
Sign up to set email alerts
|

"Effect of Monosodium Glutamate Substitutes on Physiochemical, Microbiological and Sensory Properties of Fried Chicken Breast Strips"

Abstract: The effect of replacement monosodium glutamate (MSG) with 1:1 ratio mixture of sugar and salton physiochemical, microbiological and sensory properties deep fat fried chicken breast strips during frozen storage (-18°C) for 90 days was investigated. Results showed that control samples had statistically higher moisture,carbohydrate and ash contents than the treated fried samples, moisture, carbohydrate and ash contents for all treatments and slightly decreased as storage period progressed. The crude protein and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Whereas canned hen meat had the highest concentration mean value of chemical food additive Monosodium glutamate as flavoring agent, followed by hen minced meat, hen pannae, hen shawerma, and fried hen meat samples, and fried hen meat samples had the lower results. In comparison with previous studies, we found results of canned hen meat were lower than that obtained by 7,18 (210.80 mg/Kg.). Then pannae were higher results than those obtained by 7,21 (1.4570 mg/Kg.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Whereas canned hen meat had the highest concentration mean value of chemical food additive Monosodium glutamate as flavoring agent, followed by hen minced meat, hen pannae, hen shawerma, and fried hen meat samples, and fried hen meat samples had the lower results. In comparison with previous studies, we found results of canned hen meat were lower than that obtained by 7,18 (210.80 mg/Kg.). Then pannae were higher results than those obtained by 7,21 (1.4570 mg/Kg.…”
Section: Discussioncontrasting
confidence: 89%
“…Circulatory hazards, cardiac effects, muscular damage, gastrointestinal hazards, and neurological hazards are more prevalent. 7,18 chemical Food additive Monosodium glutamate as flavoring agent causes genetic damage, free radicals to cause harm effect to the cells. 7,19,20 According to the results obtained in Table 1, there were differences in chemical food additive Monosodium glutamate as flavoring agent values in the examined processed hen meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken meat is among the foods preferred by consumers in Egypt and throughout the universe because of its nutritional value and reasonable price (Abdelrahman et al, 2020 andShaltout, 2022). However, with the increased consumption of meat and meat products, the incidence of foodborne disease outbreaks linked to meat has increased significantly.…”
Section: Introductionmentioning
confidence: 99%